Overview on the Current Status of Hydrogen Energy Research and Development in India - Medisetty, Venkata Manikanta; Kumar, Ravinder; Ahmadi, Mohammad Hossein; Vo, Dai-Viet N.; Ochoa, A. A. V.; Solanki, Rajniesh (Chemical engineering & technology, 2020)
The energy demand for the automobile and industrial sectors is increasing drastically worldwide. Conventional sources will no longer fulfil the growing energy demand and environmental pollution is a big concern. Thus, an alternative fuel for vehicles is highly required. The focus is shifted on renewable energy sources like hydrogen, which is abundant in nature. This review examines the continuous progress of hydrogen regarding production and storage techniques in India. Current studies and ongoing projects are summarized projecting the status of production, storage, and application of hydrogen. Challenges like infrastructure development, distribution, policies, cost, and public acceptance as obstacles for the commercialization of hydrogen‐powered vehicles in the Indian market are analyzed. Hydrogen is currently proving its potency as a sustainable and clean energy carrier with high specific energy and zero polluting energy sources. The progress of hydrogen energy research and development regarding production and storage techniques in India is reviewed discussing current studies and ongoing projects. Challenges related to the promotion of hydrogen in India are highlighted.